2012
DOI: 10.2478/s13533-011-0074-7
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between the structural pattern and the development of the hydrographic network in a portion of the Western Thessaly Basin (Greece)

Abstract: Abstract:In the context of the present study the structural pattern in the Western Thessaly Basin (Greece) has been examined, based on structural data collected from the entire study area that were further correlated to the hydrographic network. The structural pattern of the area was revealed from tectonic analysis. Additionally, the topography, stratigraphy and sedimentology of the study area were taken into account. GIS techniques were used to map the spatial distribution of the geological and tectonic featu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…These are the hilly-mountainous region, with an absolute altitude ranging from 200 m up to more than 2,000 m and the lowland region, with an absolute altitude up to 200 m. These areas occupy 62.12 % and 37.88 % of the overall area, respectively. The hydrographic network is well developed with a significant surface runoff [28,29].…”
Section: Study Areamentioning
confidence: 97%
See 1 more Smart Citation
“…These are the hilly-mountainous region, with an absolute altitude ranging from 200 m up to more than 2,000 m and the lowland region, with an absolute altitude up to 200 m. These areas occupy 62.12 % and 37.88 % of the overall area, respectively. The hydrographic network is well developed with a significant surface runoff [28,29].…”
Section: Study Areamentioning
confidence: 97%
“…Thessaly is the most intensely cultivated and productive agricultural plain in Greece, mainly crossed by the Pinios River and surrounded by high mountains [29]. This plain is subdivided by a group of hills into two hydrogeological basins, the Western (Trikala-Karditsa plain) and the Eastern (Larisa plain) [28].…”
Section: Study Areamentioning
confidence: 99%
“…Of course a detailed knowledge of this boundary condition may lead to an improvement of the summary graph. -in general, a better analysis of the geomechanical properties of Flysch and Marl [59] as well as a complete analysis of the geological context [60] may lead to a great improvement in risk analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In our experiments concerning the automatic detection of the previously mentioned structures, we used the DEM corresponding to contour interval of 4 m (Figure 4(a)) aiming to accurately track the linearcurvilinear lineaments. Then, we digitized the normal faults on Tinos from the IGME map (Tinos-Yaros sheet, 1:50,000) and we overlaid the rose diagrams that resulted from the processing of the tectonic field measurements based on the methodology applied in previous works (Kamberis et al, 2012;Kokinou, 2015). Based on the results of (a) the automatic detection (Figure 7(a)) of the linear-curvilinear lineaments in the study area, (b) the already available geological information of the IGME map (Figures 2 and 7(b)) and (c) the tectonic field measurements (see rose diagrams in Figure 7(b); it is concluded that NE-SW to ENE-WSW and NW-SE to WSW-ESE trending normal geological faults characterized by steep slopes (>60°) prevail in the northern sector of the study area.…”
Section: Geomorphological Featuresmentioning
confidence: 99%